2020
DOI: 10.1111/hex.13024
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of the caring encounter with the psychiatric emergency response team in the emergency medical service—A qualitative interview study

Abstract: Background Mental illnesses are increasing in the population; consequently, the number of psychiatric emergencies handled by the emergency medical services (EMS) has also increased. Alternative response systems have been developed and evaluated, but there is still a lack of knowledge concerning the patients' experiences of being cared for in the EMS by a psychiatric emergency response unit (In Swedish: Psykiatrisk Akut Mobilitet [PAM]). Objective The aim of this study was to explore patients' experiences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
(65 reference statements)
3
27
0
1
Order By: Relevance
“…The biases of nurses affect their care attitudes and affect the completeness of emergency evaluation and suitability of subsequent management of psychiatric patients. These results are similar to the studies of Clarke et al, Pelleboer-Gunnink et al, and Lindström et al [ 24 , 25 , 26 ]. The awareness and biases in triage nurses may affect the collection of consultation information, resulting in inappropriate triage decisions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The biases of nurses affect their care attitudes and affect the completeness of emergency evaluation and suitability of subsequent management of psychiatric patients. These results are similar to the studies of Clarke et al, Pelleboer-Gunnink et al, and Lindström et al [ 24 , 25 , 26 ]. The awareness and biases in triage nurses may affect the collection of consultation information, resulting in inappropriate triage decisions.…”
Section: Discussionsupporting
confidence: 93%
“…These results echoed those of previous studies in which emergency department nurses felt that they lack communication skills [ 31 ]. Psychiatric patients described how professional nurses may be good at resuscitation but not at communication and listening [ 26 ], showing a lack of nurse–patient communication skills and indicating that more communication technique training is warranted [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because mental health disorders are becoming a nationwide healthcare concern, alternative approaches have been introduced. Evaluations of these approaches showed that a first‐line response that included combined psychiatric and somatic expertise was beneficial in providing advanced medical assessments, when attending individuals with severe mental health issues, behavioural crises or suicidal tendencies (Boscarato et al., 2014; Bouveng et al., 2017; Evangelista et al., 2016; Huppert & Griffiths, 2015; Lindström et al., 2020; Nordentoft et al., 2002; Watson et al., 2008). Therefore, the Board of Health in Region of Skåne decided to initiate, for a limited period of time, a project that included an additional pre‐hospital emergency psychiatric unit in the southeast part of Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, patients’ experiences of specialist psychiatric EC units are found to contribute to a care without fear of being dismissed, ignored and judged. 41 Summarised, the need to develop and expand the RNs’ understanding of the holistic aspects of their professional role is important and should be taken into account in when arranging EC. This is especially so when the care of people with mental illness in emergency departments may increase 6,7 and be adversely affected by diagnostic overshadowing and avoidance by clinical staff.…”
Section: Discussionmentioning
confidence: 99%